Review Of Workload The Assembling Part Of The Inpatient Medical Record With The FTE At Al-Ihsan Hospital: Tinjauan Beban Kerja Bagian Assembling Rawat Inap Dengan Metode FTE Di RSUD Al-Ihsan - Pujilestari, Intan; Indriyani, Fitri (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
The workload on inpatient assembling officers is not in accordance with the number of existing workers, resulting in work fatigue and can result in a decrease in work productivity thereby affecting the quality of hospital health services. The purpose of this study was to determine the Workload of the Inpatient Medical Record Assembling Section with the Full Time Equivalent Method to Support Service Effectiveness at Al-Ihsan Hospital, West Java. The research method used is a descriptive method with a quantitative and qualitative analysis approach (Combination Method). Data collection techniques with observation, interviews and documentation studies. The research instrument used stationery, stopwatch, calculator, interview guide, camera and observation sheet. The results of the assembling implementation were 0.10% of the 98 files that were not in accordance with the SOP. The classification of assembling officers is not in accordance with the applicable provisions. HR needs for the inpatient assembling section using the Full Time Equivalent method for 3 people. Employee effectiveness has not been effective in terms of quality and quantity. Recruitment of manpower and training needs to be done in the development of knowledge and completion of work. It is suggested that it is necessary to realize human resource needs in accordance with existing standards and to carry out workload analysis as a benchmark in completing existing work in the inpatient assembling section which supports the effectiveness of services at Al-Ihsan Hospital, Bandung Regency, West Java Province.